Virtually reassembling Angkor-style Khmer temples. Issue 1 (2015) - Schäfer, Anja; Bock, Georg; Sanday, John; Leitte, Heike
Abstract Cambodian temples are severely damaged and their reconstruction is complex. Conservators are challenged by a magnitude of stones of unknown original position. Specialists resolve this large-scale puzzle by analyzing each stone, using their experience and knowledge of Khmer culture. Then a trial and error approach is applied which has disadvantages. The weight of the stones of up 1000 kg complicates their movement and opposes a safety hazard to workers. Additionally the stones' relocation should be reduced to a minimum as it promotes their deterioration. This motivated the development of a virtual approach, as computer algorithms lead to a potential solution in less time, thereby drastically reducing the amount of work. The basis for this virtual puzzle are high-resolution 3D models of 135 stones. These stones have an approximately cuboidal form and often feature indentations that are exploited by the algorithm to accelerate the matching process. The general idea is to (1) simplify the high-resolution models, (2) test all feasible combinations and (3) match best combinations and validate the results. Close collaboration with specialists on site ensures overall algorithmic correctness.